Divergence Between Sympatric Rice- and Maize-Infecting Populations of Rhizoctonia solani AG-1 IA from Latin America - Gonzalez-Vera, A. D.; Bernardes-de-Assis, J.; Zala, M.; McDonald, B. A.; Correa-Victoria, F.; Graterol-Matute, E. J.; Ceresini, P. C. [UNESP] (Amer Phytopathological Soc, 2010)
The basidiomycetous fungus, Rhizoctonia solani anastomosis group (AG)-1 IA is a major pathogen in Latin America causing sheath blight (SB) of rice Particularly in Venezuela. the fungus also Causes banded leaf and sheath blight (BLSB) oil maize, which is considered all emerging disease problem where maize replaced traditional rice-cropping areas or is now planted in adjacent. fields Our goals in this study Were 10 elucidate (i) the effects of host specialization on gene flow between sympatric and allopatric rice and maize-infecting fungal populations and (ii) the reproductive mode of the fungus, looking for evidence of recombination in total, 375 isolates of R. solani AG1 IA sampled from three sympatric rice and maize fields in Venezuela (Porutuguesa State) and two allopatric rice fields from Colombia (Meta State) and Panama (Chiriqui State) were genotyped Using, 10 microsatellite loci Allopatric populations from Venezuela. Colombia. and Panama were significantly differentiated (Phi(ST), of 0 16 to 0 34). Partitioning of the genetic diversity indicated differentiation between sympatric populations from different host species, with 17% of the total genetic variation distributed between hosts while only 3 to 6% wits distributed geographically among the sympatric Venezuelan Fields We detected symmetrical historical migration between the rice- and the maize-infecting populations from Venezuela Rice- and maize-derived isolates were able to infect built rice and maize but were more aggressive Oil their original hosts, consistent with host specialization. Because the maize- and rice-infecting populations are still cross-pathogenic, we postulate that the genetic differentiation was relatively recent and mediated via a host shift. An isolation with nu.-ration analysis indicated that the maize-infecting population diverged from the rice-infecting population between 40 and 240 years ago Our findings also suggest that maize-infecting Populations have a mainly recombining reproductive system whereas the rice-infecting Populations have a Mixed reproductive system in Latin America